2012
DOI: 10.1002/asia.201200507
|View full text |Cite
|
Sign up to set email alerts
|

Opp‐Dibenzoporphyrins as a Light‐Harvester for Dye‐Sensitized Solar Cells

Abstract: New opp-dibenzoporphyrins were prepared in a concise method that was based on a Pd(0)-catalyzed cascade reaction. These porphyrins, which contained carboxylic-acid linker groups on benzene rings that were fused to the porphyrin at their β,β'-positions, were examined as sensitizers for dye-sensitized solar cells for the first time. Whereas all of the porphyrins showed solar-energy-to-electricity conversion, an opp-dibenzoporphyrin with conjugated carboxylic-acid linkers displayed the highest conversion efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 69 publications
0
13
0
Order By: Relevance
“…Our group has been engaged in the development of concise and versatile synthetic methods to access β‐functionalized π‐extended porphyrins . In previous work, we showed that opp ‐dibenzoporphyrins with pull–pull structures could convert solar energy to electricity with moderate efficiencies ( η =1.5–3.1 %) . In this work, we present the synthesis, characterization, and evaluation of a series of monobenzoporphyrins as sensitizers in DSSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Our group has been engaged in the development of concise and versatile synthetic methods to access β‐functionalized π‐extended porphyrins . In previous work, we showed that opp ‐dibenzoporphyrins with pull–pull structures could convert solar energy to electricity with moderate efficiencies ( η =1.5–3.1 %) . In this work, we present the synthesis, characterization, and evaluation of a series of monobenzoporphyrins as sensitizers in DSSCs.…”
Section: Introductionmentioning
confidence: 99%
“…36) were synthesized through a Pd 0 -catalyzed cascade reaction. 111 These opp-dibenzoporphyrins (112)(113)(114)(115)(116) were evaluated for the rst time as light harvesters for dye-sensitized solar cells. These porphyrins displayed moderate solar energy-to-electricity conversion efficiencies of 1.54-3.14%.…”
Section: Fused Porphyrinsmentioning
confidence: 99%
“…118 These opp-dibenzoporphyrins (72)(73)(74)(75)(76) were evaluated for the first time as a light harvester for dye-sensitized solar cells. These porphyrins displayed moderate solar energy-to-electricity conversion efficiencies of 1.54%-3.14%.…”
Section: Fused Porphyrinsmentioning
confidence: 99%
“…The higher efficiency of 118 than that of 117 was attributed to the longer electron lifetime and higher amount of dye adsorption onto the TiO2 surface. The efficiency was found to improve up to 4.83% (117) and 6.07% (118) when CDCA was incorporated in the dye solution. The electrochemical impedance data indicated that the electron lifetime was improved by the co-adsorption of CDCA, which was attributed to the improvement in both V oc and J sc .…”
Section: B Dimethylphenyl Donor Groupmentioning
confidence: 99%
See 1 more Smart Citation